A model of collaborative process planning system (e-CAPP) - Mijodrag Milošević; Dejan Lukić; Stevo Borojević; Goran Šimunović; Aco Antić (Tehnički Vjesnik, 2017)
The current tendency of global competitiveness requires the development of distributed application systems that are used in the product design, the production preparation, as well as directly in the manufacturing processes. In this way, distributed design and production environments created actually exceed traditional physical and time constraints. The application of internet/intranet technologies enables the connection and integration of geographically dislocated designers, experts, systems, resources and services. After analysing new tendencies in planning and preparing the distributed manufacturing, a need to develop a collaborative system in the area of process planning is identified. Activities related to process planning in distributed environments are often realized by applying the extended CAPP system whose knowledge base is increased and improved by the knowledge of geographically dislocated experts. The e-CAPP represents exactly such a collaborative system which can be effectively applied in the area of process planning.